2021
DOI: 10.1029/2020jc016489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hurricane Wind Field Variability on Real‐Time Forecast Simulations of the Coastal Environment

Abstract: Tropical cyclones are a significant and increasing natural hazard for human life and infrastructure along many coastlines throughout the world. Atlantic Ocean hurricanes deliver powerful conditions to the east and Gulf coasts of North America annually and are the most destructive natural disaster in the United States (Grinsted et al., 2019). The frequency and intensity of these storms are projected to increase with future climate warming and longer storm formation periods (Knutson et al., 2010). During these s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The geographic configuration surrounding Oregon Inlet, combined with prevailing winds from the southwest and northeast, maximizes fetch length over the Pamlico Sound and enhances wind induced setup/setdown (Mulligan et al, 2015;Safak et al, 2016). Previous observations and numerical simulations have shown that winds may alter water levels in the sound by more than 2 m, a magnitude that surpasses the tidal range within the sound by at least an order of magnitude (Clunies et al, 2017;Mulligan et al, 2015;Rey & Mulligan, 2021;Safak et al, 2016). Spore & Brodie, 2017;Spore et al, 2019).…”
Section: Study Sitementioning
confidence: 98%
“…The geographic configuration surrounding Oregon Inlet, combined with prevailing winds from the southwest and northeast, maximizes fetch length over the Pamlico Sound and enhances wind induced setup/setdown (Mulligan et al, 2015;Safak et al, 2016). Previous observations and numerical simulations have shown that winds may alter water levels in the sound by more than 2 m, a magnitude that surpasses the tidal range within the sound by at least an order of magnitude (Clunies et al, 2017;Mulligan et al, 2015;Rey & Mulligan, 2021;Safak et al, 2016). Spore & Brodie, 2017;Spore et al, 2019).…”
Section: Study Sitementioning
confidence: 98%
“…It has been applied throughout the world in coastal contexts similar to this one (e.g. Mulligan et al 2008Mulligan et al , 2010Garcia et al 2015;Hasan et al 2016;Peng and Bradon 2016;de Mendoza et al 2018;Rey and Mulligan 2021). Recent coupled Delft3D FLOW/SWAN configurations have also been successfully applied to this study region by Rautenbach (2020), de Vos et al (2021) and Rautenbach et al (2020b).…”
Section: Numerical Modelsmentioning
confidence: 99%
“…These magnitudes were slightly over-predicted relative to observations but were accurate in direction and timing, and highlight the importance of wave forcing in simulating coastal currents, particularly during large wave events. Rey and Mulligan (2021) also utilised Delft3D Flow and SWAN to simulate the coastal hydrodynamics near a stretch of North Carolina shoreline during a hurricane. Although the focus of that study was on the effect of different wind forcing on the quality of the simulations, the authors also noted the importance of wave forcing on currents in certain parts of their domain, especially during large wave events.…”
Section: Existing Knowledge Of the Circulationmentioning
confidence: 99%
“…This one-way nesting approach has been successfully used in other coastal areas. Most recently, a configuration of Delft3D Flow [45,46] and SWAN [47] was implemented by [48], in a similar application to this study, to assess the influence of varying wind fields on forecasts of coastal dynamics near North Carolina, USA. Boundary and atmospheric forcing from various global models were used to provide appropriately downscaled wave, current and water level estimates.…”
Section: The Case For a Coastal Modelmentioning
confidence: 99%
“…Delft3D Flow has been extensively used in ocean and coastal domains [56] and the reliability of its code variously established [57][58][59]. The model has been successfully applied in cases similar to the one in this study (e.g., [48,50,53,60,61]).…”
Section: Numerical Modelsmentioning
confidence: 99%